HUBUNGAN KONSEP DIRI DAN DUKUNGAN SOSIAL ORANG TUA TERHADAP KEMATANGAN KARIER SISWA MA MADANIA - Azis Rahmat Ma’rufi; Mujidin; Yuzarizon (Wahana Islamika: Jurnal Studi Keislaman, 2020)
The purpose of this study is to test: 1) The relationship between self-concept and parents' social support to the career maturity of MA Madania students; 2) The relationship between self-concept and career maturity of MA Madania students; and 3) The relationship between social support of parents to the career maturity of MA Madania students. This research is a quantitative research. The sample of this research was grade XII students in MA Madania, totaling 53 students taken using a saturation sampling technique. Data collection techniques using a Likert scale. Data were analyzed by multiple regression analysis. The results of the analysis obtained an Fcount of 27.325 with a significance of 0.000 < 0.05, meaning that there is a relationship between self-concept and social support from parents to career maturity. Based on the results of the study, it can be concluded: 1) There is a positive influence betweenself-concept and parental social support on the career maturity of MA Madania students; 2) There is a positive influence between self-concept on the career maturity of MA Madania students; and 3) There is a positive influence between parental social support on the career maturity of MA MAdania students.